Early Eocene snakeflies (Raphidioptera) of western North America from the Okanagan Highlands and Green River Formation - Archibald, S. Bruce; Makarkin, Vladimir N. (Zootaxa, 2021)
Four new species of Raphidiidae are described from the early Eocene of western North America: Megaraphidia antiquissima sp. nov. from McAbee, M. ootsa sp. nov. from Driftwood Canyon, M. hopkinsi sp. nov. from the Allenby Formation (all from British Columbia, Canada), M. klondika sp. nov. from Republic (Washington, United States of America). Archiinocellia Handlirsch, 1910, Archiinocellia oligoneura Handlirsch, 1910 from Horsefly River (British Columbia, Canada), and A. protomaculata (Engel, 2011), comb. nov., from the Green River Formation (Colorado, United States of America) are redescribed. Archiinocellia is assigned to Raphidiidae, sit. nov. The apparent absence of sclerotized gonocoxites 9 in the Archiinocellia protomaculata male is probably plesiomorphic at the family level. As some modern snakeflies do not require a cold interval to complete their development and Eocene Inocelliidae and Raphidiidae lived in regions of warm winters (especially A. protomaculata), adaptation to cold winters in many modern snakeflies is a post-Eocene phenomenon. Eocene Raphidiidae of Europe (Priabonian) differ greatly from those of North America (Ypresian and Priabonian). This pattern might reflect dispersal in either direction or ranges established prior to continental separation. Eocene Inocelliidae of Europe (Priabonian), however, are more similar to those of North America (Ypresian and Lutetian).